Hubungan Pengetahuan dengan Perilaku Protokol Kesehatan sebagai Upaya Preverentif Covid 19 pada Civitas Akademika di Universitas Malahayati Bandar Lampung - Eka Trismiyana; Umi Romayati Keswara; A'raaf Almaera Febrian (Universitas Malahayati Lampung, 2022)
ABSTRACT: ATTITUDE RELATIONSHIP WITH HEALTH PROTOCOL BEHAVIOR AS A PREVERENTIVE EFFORT FOR COVID 19 IN ACADEMIC CIVITY AT MALAHAYATI UNIVERSITY BANDAR LAMPUNG Introduction: Indonesia is showing a large number of confirmed cases and deaths in the COVID19 outbreak, and prevention strategies are needed for the more severe spread of the disease. Lampung Province the number of cases of covid 19 as of December 2020 has reached 4,871 patients who have been confirmed to have covid 19 (Lampung Provincial Health Office, 2020). As for the details of 78 new cases, namely in Bandarlampung City, 33 cases; South Lampung Regency 15 cases; East Lampung 8 cases; and North Lampung 5 cases. Then, there were 2 cases in Tulang Bawang Regency; Pringsewu 3 cases; 2 cases bid; West Coast 1 case; West Lampung 3 cases; and Central Lampung 6 cases. Objective: To determine the relationship between attitudes and the behavior of the 5M health protocol as a pre-incentive for COVID 19 to the Academic Community at Malahayati University, Bandar Lampung in 2021 Methods: This type of research is quantitative. The design in this study used an analytical survey design with a cross-sectional approach. The population in this study were all members of the community at Malahayati University, Bandar Lampung, totaling 3726 respondents. Univariate and bivariate data analysis used the chi-square test.Result : From 362 respondents who have poor category knowledge as many as 194 respondents (53.6%), having applied category behavior as many as 228 respondents (63.0%). The results of the chi square test obtained a p-value of 0.000 (≤0.05), which means that there is a relationship between knowledge and the behavior of health protocols as a preventive effort for COVID.Suggestion: Improve campus facilities to support teaching and learning activities during the COVID-19 outbreakKeywords : Knowledge, 3M Health Protocol Behavior, Preventive Efforts INTISARI: HUBUNGAN PENGETAHUAN DENGAN PERILAKU PROTOKOL KESEHATAN SEBAGAI UPAYA PREVERENTIF COVID 19 PADA CIVITAS AKADEMIKA DI UNIVERSITAS MALAHAYATI BANDAR LAMPUNG TAHUN 2021 Pendahuluan: Indonesia menunjukkan sejumlah besar kasus dan kematian yang dikonfirmasi dalam wabah COVID19, dan diperlukan strategi pencegahan untuk penyebarluasan penyakit yang lebih parah. Provinsi Lampung angka kejadian covid 19 per Desember 2020 telah menginjak angka 4.871 pasien yang terkonfirmasi mengalami covid 19 (Dinkes Provnsi Lampung, 2020) Adapun rincian 78 kasus baru yakni di Kota Bandarlampung 33 kasus; Kabupaten Lampung Selatan 15 kasus; Lampung Timur 8 kasus; dan Lampung Utara 5 kasus. Lalu, Kabupaten Tulang Bawang 2 kasus; Pringsewu 3 kasus; Pesawaran 2 kasus; Pesisir Barat 1 kasus; Lampung Barat 3 kasus; dan Lampung Tengah 6 kasus.Tujuan: Untuk diketahui hubungan sikap dengan perilaku protokol kesehatan 5M sebagai upaya preverentif COVID 19 pada Civitas Akademika di Universitas Malahayati Bandar Lampung Tahun 2021Metode: Jenis penelitian kuantitatif, Rancangan dalam penelitian ini menggunakan desain Survei Analitik dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh civitas di Universitas Malahayati Bandar Lampung sebanyak 3726 responden. Analisa data univariat dan bivariat menggunakan uji chi square.Hasil : Dari 362 responden yang memiliki pengetahuan kategori kurang baik sebanyak 194 responden (53,6%), memiliki perilaku kategori menerapkan sebanyak 228 responden (63,0%). Hasil uji chi square didapat nilai p-value 0,000 (≤0,05) yang artinya ada hubungan pengetahuan dengan perilaku protokol kesehatan sebagai upaya preverentif COVID.Saran : Meningkatkan fasilitas saranaprasarana kampus agar menunjang kegiatan belajar mengajar selama terdapat wabah COVID-19. Kata Kunci : Pengetahuan, Perilaku Protokol Kesehatan 3M, Upaya Preverentif